Evaluation of Chrisofix® Chest Orthosis Application in Patients with Traumatic Rib Fractures - Işıklı, Ayşe Gökce; Yanık, Fazlı; Karamustafaoğlu, Yekta Altemur; Yörük, Yener (Bangladesh Journal of Medical Science, 2024)
Background: The Chrisofix® Chest Orthosis is an effective and easy to use device for the treatment of rib fractures. It is used as a supportive treatment to reduce the pain levels and complication risks of the patients. Methods: Patients hospitalized with the diagnosis of rib fractures in the Thoracic Surgery Service of a university hospital were retrospectively scanned in an online computer program between October 2018 and October 2021. The study sample consisted of patients with the treatment (30) and control (30) groups. Results: Visual Analog Scale and incidence of atelectasis of the patients in the experimental group (The Chrisofix® Chest Orthosis) is statistically significantly lower than the control group (P < 0.05). In both the experimental and control groups, no statistically significant difference was found between the variables of patient’s demographic and clinical characteristics (p > 0.05). Conclusions: In the study, with the use of The Chrisofix® Chest Orthosis, a significant decrease was observed in the Visual Analog Scale and the incidence of atelectasis. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 83-88